2008
DOI: 10.1176/appi.ajp.2007.07020352
|View full text |Cite
|
Sign up to set email alerts
|

Association of Low Striatal Dopamine D 2 Receptor Availability With Nicotine Dependence Similar to That Seen With Other Drugs of Abuse

Abstract: Similar to other types of substance abuse, nicotine dependence is associated with low availability of dorsal striatal D(2)/D(3) receptors. In contrast to previous findings on abstinent alcohol-dependent patients, nicotine craving seems to be maintained by a region-specific shift in D(2)/D(3) receptor availabilities, with higher availability within the ventral striatum but lower availability within the anterior cingulate and inferior temporal cortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
146
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(166 citation statements)
references
References 45 publications
13
146
1
2
Order By: Relevance
“…These results doubly dissociate the role of the D1R vs. D2R in nicotine motivation, such that the motivational response to withdrawal in dependent mice is D2R-mediated and acute nicotine motivation is D1R-mediated. These results are in line with previous studies showing that drug-dependent human subjects have marked decreases in D2R availability (34) and presumably in DA release (35), which is consistent with the hypothesis that a pattern of DA activity signals nicotine motivation and the present results showing that nicotine-dependent and -withdrawn mice have a decrease in tonic activity of VTA DA neurons. Furthermore, animal studies have shown that D1R antagonism blocks nicotine motivation in nondependent mice (36).…”
Section: Discussionsupporting
confidence: 93%
“…These results doubly dissociate the role of the D1R vs. D2R in nicotine motivation, such that the motivational response to withdrawal in dependent mice is D2R-mediated and acute nicotine motivation is D1R-mediated. These results are in line with previous studies showing that drug-dependent human subjects have marked decreases in D2R availability (34) and presumably in DA release (35), which is consistent with the hypothesis that a pattern of DA activity signals nicotine motivation and the present results showing that nicotine-dependent and -withdrawn mice have a decrease in tonic activity of VTA DA neurons. Furthermore, animal studies have shown that D1R antagonism blocks nicotine motivation in nondependent mice (36).…”
Section: Discussionsupporting
confidence: 93%
“…We also examined D 2 receptor involvement in chronic nicotine withdrawal aversions. The DA D 2 receptor has been implicated in nicotine dependence (Fehr et al, 2008) and withdrawal (Laviolette et al, 2008). Our results show that acute aversive and chronic rewarding nicotine lead to opponent a-and bprocesses and that dopaminergic signaling, specifically at the D 2 receptor, mediates the opponent motivational process of chronic aversive but not acute rewarding nicotine.…”
Section: Introductionmentioning
confidence: 60%
“…[ fallypride PET imaging study, nicotine-dependent smokers displayed signifi cantly less availability of D2/D3 receptors within the bilateral putamen, functionally covering parts of the dorsal striatum, compared to never-smoking subjects [83] .…”
Section: Pet Studies Of Postsynaptic Da Receptorsmentioning
confidence: 97%
“…labeled benzamide derivative that binds reversibly to D2 receptors [81] . In PET imaging with [ 18 F] FCP, Nader and colleagues [82] found that the baseline D2 receptor availability is negatively correlated with the rate of cocaine self-administration.[ fallypride PET imaging study, nicotine-dependent smokers displayed signifi cantly less availability of D2/D3 receptors within the bilateral putamen, functionally covering parts of the dorsal striatum, compared to never-smoking subjects [83] .[ 18 F] desmethoxyfallypride ([ 18 F] DMFP), another selective D2/D3 receptor antagonist, has also been developed and used to fi nd that a low availability of D2/3 receptors in the ventral striatum and adjacent putamen is associated with a high level of craving for alcohol [33] .For the D1 receptor, [ 11 C] NNC 112, a new benzazepine [(+)-8-chloro-5-(7-benzofuranyl)-7-hydroxy-3-methyl-2,3,4,5-tetra-hydro-lH-3-benzazepine], has been reported to be a useful PET radioligand for the quantitation of D1 receptors in humans [84] , and its D1 receptor selectivity has recently been re-evaluated [85] . With PET and the radiotracer [ 11 C] NNC 112, Martinez et al [86] found no difference between cocaine abusers and normal controls.…”
mentioning
confidence: 99%